Effects of Cover Crops on Pratylenchus penetrans and the Nematode Community in Carrot Production - Grabau, Zane J (Journal of nematology, 2017)
Cover cropping is a common practice in U.S. Midwest carrot production for soil conservation, and may affect soil ecology and plant-parasitic nematodes-to which carrots are very susceptible. This study assessed the impact of cover crops-oats (Avena sativa), radish (Raphanus sativus) cv. Defender, rape (Brassica napus) cv. Dwarf Essex, and a mixture of oats and radish-on plant-parasitic nematodes and soil ecology based on the nematode community in Michigan carrot production systems. Research was conducted at two field sites where cover crops were grown in Fall 2014 preceding Summer 2015 carrot production. At Site 1, root-lesion (Pratylenchus penetrans) and stunt (Tylenchorhynchus sp.) nematodes were present at low population densities (less than 25 nematodes/100 cm3 soil), but were not significantly affected (P > 0.05) by cover crops. At Site 2, P. penetrans population densities were increased (P ≤ 0.05) by 'Defender' radish compared to other cover crops or fallow control during cover crop growth and midseason carrot production. At both sites, there were few short-term impacts of cover cropping on soil ecology based on the nematode community. At Site 1, only at carrot harvest, radish-oats mixture and 'Dwarf Essex' rape alone enriched the soil food web based on the enrichment index (P ≤ 0.05) while rape and radish increased structure index values. At Site 2, bacterivore abundance was increased by oats or radish cover crops compared to control, but only during carrot production. In general, cover crops did not affect the nematode community until nearly a year after cover crop growth suggesting that changes in the soil community following cover cropping may be gradual